Conceptualizing Creativity and Strategy in the Work of Professional Songwriters. Issue 5 (20th October 2017) - Long, Paul; Barber, Simon
Abstract: Drawing upon interviews conducted as part of the Sodajerker on Songwriting podcast this paper explores professional songwriting as musical labor. It explores how songwriters conceptualize creativity and what strategies they employ for the delivery of original songs. It argues that individuals evince a faith in their own autonomy in the face of the demands of form and industry, expressing intuitive concepts of inspiration and practical insights into the nature of their work as work. The paper suggests that achieving and maintaining success is affirmed in a conjunction of value that is both economic and aesthetic, personal and public.